1994
DOI: 10.1002/syn.890170311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal cocaine exposure upon postnatal development of neostriatal dopaminergic function

Abstract: Pregnant rats were injected twice daily with 20 mg/kg cocaine (or saline) from gestational day 10 to parturition. Brains from offspring were examined with quantitative receptor autoradiography [D1 receptor (D1R), D2 receptor (D2R) and dopamine transporter (DAT)] and quantitative in situ hybridization [D1R mRNA, D2R mRNA, preproenkephalin (PPE) mRNA] for markers of neostriatal dopaminergic function. Prenatal cocaine exposure did not alter postnatal development of striatal D1R sites, but D1R mRNA levels were red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 33 publications
5
37
3
Order By: Relevance
“…In contrast with the effects of dopamine receptor antagonists, the behavioral changes observed in rodents after prenatal exposure to cocaine described previously were not associated with consistent or persistent changes in the density or in the affinity of dopamine receptors (Mayfield et al, 1992;Leslie et al, 1994;Scalzo et al, 1990). Thus, prenatal cocaine exposure resulted in increases in striatal D 2 receptor ligand binding at postnatal days 6-35 (Leslie et al, 1994) due to an increased D2 ligand affinity (Scalzo et al, 1990), and exhibited a corresponding increased sensitivity to the D2 agonist quinpirole (Moody et al, 1992). However, these changes did not appear to extend into adulthood.…”
Section: Introductioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In contrast with the effects of dopamine receptor antagonists, the behavioral changes observed in rodents after prenatal exposure to cocaine described previously were not associated with consistent or persistent changes in the density or in the affinity of dopamine receptors (Mayfield et al, 1992;Leslie et al, 1994;Scalzo et al, 1990). Thus, prenatal cocaine exposure resulted in increases in striatal D 2 receptor ligand binding at postnatal days 6-35 (Leslie et al, 1994) due to an increased D2 ligand affinity (Scalzo et al, 1990), and exhibited a corresponding increased sensitivity to the D2 agonist quinpirole (Moody et al, 1992). However, these changes did not appear to extend into adulthood.…”
Section: Introductioncontrasting
confidence: 49%
“…Furthermore, prenatal exposure of rodents to dopamine receptor inhibition affects maze learning and motor activity levels (Clark et al, 1970) as well as sensitivity to dopamine antagonists when exposed offspring were tested as adults (Golub and Kornetsky, 1975). In contrast with the effects of dopamine receptor antagonists, the behavioral changes observed in rodents after prenatal exposure to cocaine described previously were not associated with consistent or persistent changes in the density or in the affinity of dopamine receptors (Mayfield et al, 1992;Leslie et al, 1994;Scalzo et al, 1990). Thus, prenatal cocaine exposure resulted in increases in striatal D 2 receptor ligand binding at postnatal days 6-35 (Leslie et al, 1994) due to an increased D2 ligand affinity (Scalzo et al, 1990), and exhibited a corresponding increased sensitivity to the D2 agonist quinpirole (Moody et al, 1992).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, this mechanism is unlikely on the basis of previous findings that prenatal exposure to cocaine (1) did not affect D 1 mRNAs (DeBartolomeis et al, 1994) or receptor binding in the striatum, nucleus accumbens, or ventral tegmental area (Leslie et al, 1994) and (2) resulted in decreased D 1 receptor G-protein coupling in the striatum, anterior cingulate, and frontal cortex (Wang et al, 1995b;Friedman et al, 1996;Levitt et al, 1997). In fact, this latter finding of reduced D 1 coupling in intravenous cocaine-exposed rabbits appears inconsistent with the present findings.…”
Section: Discussionmentioning
confidence: 90%
“…However, the results are inconsistent: one study states that adult mice with prenatal cocaine exposure (GD 13-21) showed a reduction of DAT in the striatum [44], whereas other reports suggest that prenatal cocaine exposure (GD 18-21) resulted in a transient decrease in DA transporter binding in the dorsal lateral striatum at PD10 [45], with no change at adult age. Leslie et al [47] found that prenatal cocaine exposure (GD10-21) caused an increase in DAT density from PD1 to PD5; however after PD14 they observed a reduction in DAT. Different prenatal periods of exposure and doses may explain these differences.…”
Section: Discussionmentioning
confidence: 95%